Metal Oxide Nanomaterials From Fundamental to Applications - Mao, Yuanbing; Gupta, Santosh (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This is a timely collection of recent diverse work on metal oxide nanomaterials, connecting their fundamental aspects and application perspectives in a concise fashion to give a broad view of the current status of this fascinating field. This book presents eight original research articles and two comprehensive reviews to highlight the recent development and understanding of different types of metal oxide nanoparticles and their use for applications in luminescence, photocatalysis, water-oil separation, optoelectronics, gas sensors, energy-saving smart windows, etc. It presents just the tip of the iceberg of the broad, dynamic, and active fundamental research and applications in the developing field of metal oxide nanomaterials by collecting a few examples of the latest advancements.